Entre chicotes e cenouras orgânicas: cooperação, coerção e coordenação na implementação das compras da agricultura familiar para o PNAE - Bonduki, Manuel Ruas Pereira Coelho (2017)
In federalist nations, the specific institutional structure that articulates autonomy and unity (or self-rule and shared-rule, according to Elazar’s definition in 1987) has been appointed as an obstacle to the expansion of social policies and to its intergovernmental coordination. As stated by Pierson (1995), although highly interdependent, the public policies in federalist countries are only modestly coordinated. Deil Wright (1978), indicates that intergovernmental relations in federalist nations may be organized through a pattern that reinforce hierarchy and dependence of subnational governments or as patterns of negotiation and interdependence. Brazilian researchers on the theme have pointed out that the specific authority structure in terms of fiscal resources, political autonomy, and constitutional jurisdiction in each policy area have an important role on defining the IGR pattern. Besides, although Brazilian municipalities having been able to gain political autonomy, increment its fiscal share and receive constitutional jurisdiction over a wide set of policy areas, the decision on major policies regulatory milestones often remains centralized in the federal level. From this theoretical approach, in the present study we review the vertical distribution of authority in Brazilian National School Meals Program (PNAE) to then assess the coordinating federal ability in the program. This evaluation was conducted based on the case study of the implementation of a federal regulation that stipulated that at least 30% of federal resources should be spent with purchases from family farmers, preferably locals. This was, as we see it, the regulation that have most hardly revealed that a centralized decision structure in the program remained even after the decentralization that took place in 1994, when states and municipalities have started executing the program. The data analysis of 4992 municipalities (90% of the total of Brazilian local governments) from 2011 to 2014 shows that the municipalities’ adaptation to the regulation devolved in a stable and growing pattern, in local governments of all sizes and of all national regions. Although around 60% of municipalities have not reached the minimum target of 30% by 2014, there is a clear progress towards that. We thus conclude that there is a high federal coordinating capacity on the program. This capacity is built upon a centralized authority structure with little room for a cooperative approach, which determines a “inclusive authority” pattern of IGR. On the other hand, there is interdependence in the policy implementation and we could as well find situations of negotiation and cooperation, even with less institutional basis, which adds elements of Wright’s “overlapping authority model” of IGR. Finally, we recommend that the institutional design of the National School Meals Program (PNAE) should evolve to a more cooperative status, including states and municipalities in the policy decision making though negotiating arenas, creating flexible incentives, supporting local innovation, improving the role of states in local coordination and reaching for equalizing regional inequalities.